Repetitive ipsilateral painful A‐delta fibre stimuli induce bilateral LEP amplitude habituation. (29th May 2013) - Hüllemann, P.; Mahn, F.; Shao, Y.‐Q.; Watfeh, R.; Wasner, G.; Binder, A.; Baron, R.
Abstract Background In the scientific approach to central processing of pain, the habituation phenomenon has been frequently described. Recent studies mentioned electrophysiological habituation during the recording of laser‐evoked potentials (LEP). In this study we intended to test whether habituation can be reproducibly induced by repetitive painful laser stimuli and simultaneously measured with LEP. Inspired by findings from previous imaging studies that showed bilateral activation of the operculo‐insular cortices, we hypothesized that repetitive painful laser stimuli applied to one hand lead to bihemispheral LEP amplitude habituation. Methods One hundred painful stimuli were applied to the right hand of 13 healthy subjects to induce contralateral N2P2 amplitude habituation. The left hand was stimulated 25 times before and after the right‐hand stimulation to measure ispilateral LEPs; the experiment was sham controlled. Results We achieved significant contralateral N2P2 amplitude and pain habituation in all subjects. After central habituation was established, there was also a significant ispilateral N2P2 amplitude decrement (derived from the left hand) compared with baseline; in the sham condition, the N2P2 amplitude was unchanged. The pain sensation showed no habituation in both the painful stimulation condition and the sham condition. Conclusions Habituation (in the electrophysiological sense) is a physiological phenomenon that indicates normal central processing of pain in healthy controls. We showed bihemispheral N2P2 amplitude habituation after repetitive painful stimulation of the right hand. Our findings propose a bihemishperal contribution to central pain processing and pain modulation when electrophysiological habituation occurs.